HUBUNGAN PENGETAHUAN TENTANG TANDA BAHAYA KEHAMILAN DENGAN KEPATUHAN IBU HAMIL MELAKUKAN PEMERIKSAAN ANC DI PUSKESMAS SIRIWINI KABUPATEN NABIRE TAHUN 2022 - Anisa Nanang Sulistyowati; Ramla Hakim; Susana Ekariantly Renate (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2022)
The national target for achieving ANC K4 visits is 80%, the provincial target for Papua K4 is 55% and the provincial achievement is 37%. This shows that there is still a lack of achievement of provincial and national targets. The purpose of this study was to determine the relationship between knowledge about danger signs and compliance with ANC visits. Analytic survey research method with cross sectional approach. Sampling by purposive sampling. Bivariate analysis using chi square. The results obtained were a p value = 0.171 so that the results obtained meant that there was no relationship between knowledge about the danger signs of pregnancy and the compliance of pregnant women with carrying out ANC examinations at the Siriwini Health Center, Nabire Regency, in 2022.